Analysis of complaints of municipal directed network submitted to special education - Guerra, Bárbara Trevizan [UNESP]; Rovaris, Jéssica Aline [UNESP]; Mariano, Marília [UNESP]; Guidugli, Priscila Meireles [UNESP]; Rosanti, Sofia [UNESP]; Bolsoni-Silva, Alessandra Turini [UNESP] (FapUNIFESP (SciELO), 2015)
The Atendimento Educacional Especializado (AEE), in partnership with public schools, aims complementary disabled student learning in the comum school, in turn against. This study aimed to describe and analyze the contents of the referrals of teachers in public schools to the AEE, categorizing them according to sex, age, disability diagnosis, behavior problems externalizing and internalizing, disabilities learning, and others. Was contacted an institution that offers the AEE, in an interior city of São Paulo, to describe and analyze 92 referrals of children of kindergarten. The results show that most of the services performed by the AEE intended for children that do not have disabilities. In addition, 69 % of the complaints relate to externalizing behavior problems. From these data we discuss about educational practices of teachers, and alternative care for patients, whether or not students with disabilities, who have difficulties in the learning process
Análise das queixas da rede municipal encaminhadas para a Educação Especial
Keywords: Behavior; Special education; Teaching work